PENINGKATAN BRANDING & IDENTITAS ILMU KOMUNIKASI UNTIRTA MELALUI RANCANGAN VISUAL MERCHANDISE - Adhany, Allysa Farra; Rangga Gumelar (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2024)
Merchandise design has evolved into more than just functional clothing, but also as an identity element and a tool to enhance product branding. The focus of this research is on the visual merchandise design process for Untirta Communication Sciences, a state campus in Banten. Through a visual approach and graphic design, this design is made attractive and in accordance with the brand character. It is important to create a balance between innovation, brand identity, creativity and understanding trends in the branding process. This research uses a design method with several stages. In this research, it is explained that typography, visual unity, and adaptation to the target audience are key aspects in every design, especially for merchandise.